2017
DOI: 10.1016/j.joep.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

How stressful are economic competitions in the lab? An investigation with physiological measures

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 77 publications
0
30
1
Order By: Relevance
“…They also observe that the physical stress exogenously induced by a cold pressor task affects competitiveness for women but not for men. In contrast, Buckert et al (2017) find neither a higher cortisol response to computation task T nor a significant correlation between competitiveness and cortisol response.…”
Section: Introductioncontrasting
confidence: 76%
See 2 more Smart Citations
“…They also observe that the physical stress exogenously induced by a cold pressor task affects competitiveness for women but not for men. In contrast, Buckert et al (2017) find neither a higher cortisol response to computation task T nor a significant correlation between competitiveness and cortisol response.…”
Section: Introductioncontrasting
confidence: 76%
“…In contrast, Buckert et al. () find neither a higher cortisol response to computation task T nor a significant correlation between competitiveness and cortisol response.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…But the sub-sample of players who are more emotionally aroused when playing against a robot may see the competitive situation as more threatening than when opposed to a human, which affects their performance negatively. Blascovich et al (2004) and Moore et al (2012) for example have found a correlation between perception of threat, physiological reaction and performance in sport competitions; Buckert et al (2015) have shown that perceiving competition as a threat tends to decrease a player's performance in the lab. A possible interpretation cation variable.…”
Section: Resultsmentioning
confidence: 99%
“…Angelucci and Cordova (2014) investigate the impact of acute stress on cognitive performance and find that exposure to acute emotional stress may reduce women's performance and earnings compared to men's performance and earnings in a task where participants have to answer multiple-choice questions taken from the SAT. Buckert et al (2015) investigate whether having to perform in a competitive environment causes acute stress reactions. They find that participants' heart rate and arterial blood pressure are higher when performing under competitive incentives than when performing under non-competitive incentives.…”
Section: Introductionmentioning
confidence: 99%